ChIP-seq Analysis of the Global Regulator Vfr Reveals Novel Insights Into the Biocontrol Agent Pseudomonas protegens FD6 - Zhang, Qingxia; Xing, Chenglin; Kong, Xiangwei; Wang, Cheng; Chen, Xijun (Frontiers in Microbiology, 2021)
Many Pseudomonas protegens strains produce the antibiotics pyoluteorin (PLT) and 2,4-diacetylphloroglucinol (2,4-DAPG), which have antimicrobial properties. The biosynthesis of these metabolites is typically controlled by multiple regulatory factors. Vfr is a multifunctional DNA-binding regulator that modulates 2,4-diacetylphloroglucinol biosynthesis in P. protegens FD6. However, the mechanism by which Vfr regulates this process has remained unclear. In the present study, through chromatin immunoprecipitation of FLAG-tagged Vfr and nucleotide sequencing analysis, 847 putative Vfr binding sites were identified in P. protegens FD6. The consensus P. protegens Vfr-binding site predicted from a nucleotide sequence alignment is TCACA. The qPCR data showed that Vfr positively regulates the expression of phlF and phlG, which were characterized in detail. The purified recombinant Vfr bound to an approximately 240-bp fragment within the phlF and phlG upstream regions that harbor putative Vfr consensus sequences. Through a series of electrophoretic mobility shift assays, we localized Vfr binding to a 25-bp fragment that contains part of the Vfr-binding region. Vfr binding was eliminated by mutating the TACG and CACA sequences in phlF and phlG, respectively. Taken together, these results show that Vfr directly regulates the expression of the 2,4-DAPG operon by binding to upstream regions of the phlF and phlG genes. However, unlike other Vfr-targeted genes, Vfr binding in P. protegens FD6 does not require an intact binding consensus motif. Furthermore, we demonstrated that vfr expression is autoregulated in this bacterium. Taken together, our results provide novel insights into the regulatory role of Vfr in P. protegens.